Comparative safety of different recommended doses of sodium–glucose cotransporter 2 inhibitors in patients with type 2 diabetes mellitus: a systematic review and network meta-analysis of randomized clinical trials - Chen, Lu; Xue, Qingxia; Yan, Chunyan; Tang, Bingying; Wang, Lu; Zhang, Bei; Zhao, Quan (Frontiers in Endocrinology, 2023)
Objective The safety results of different recommended doses of sodium-glucose cotransporter 2 inhibitors (SGLT-2i) for patients with type 2 diabetes mellitus (T2DM) remain uncertain. This study aims to comprehensively estimate and rank the relative safety outcomes with different doses of SGLT-2i for T2DM. Methods PubMed, Embase, the Cochrane Central Register of Controlled Trials, ClinicalTrials.gov, Chinese National Knowledge Infrastructure, WanFang database, and SinoMed database were searched from the inception to 31 May 2023. We included double-blind randomized controlled trials (RCTs) comparing SGLT-2i with placebo or another antihyperglycemic as oral monotherapy in the adults with a diagnosis of T2DM. Results Twenty-five RCTs with 12,990 patients randomly assigned to 10 pharmacological interventions and placebo were included. Regarding genital infections (GI), all SGLT-2i, except for ertugliflozin and ipragliflozin, were associated with a higher risk of GI compared to placebo. Empagliflozin 10mg/d (88.2%, odds ratio [OR] 7.90, 95% credible interval [CrI] 3.39 to 22.08) may be the riskiest, followed by empagliflozin 25mg/d (83.4%, OR 7.22, 95%CrI 3.11 to 20.04)) and canagliflozin 300mg/d (70.8%, OR 5.33, 95%CrI 2.25 to 13.83) based on probability rankings. Additionally, dapagliflozin 10mg/d ranked highest for urinary tract infections (UTI, OR 2.11, 95%CrI 1.20 to 3.79, 87.2%), renal impairment (80.7%), and nasopharyngitis (81.6%) when compared to placebo and other treatments. No increased risk of harm was observed with different doses of SGLT-2i regarding hypoglycemia, acute kidney injury, diabetic ketoacidosis, or fracture. Further subgroup analysis by gender revealed no significantly increased risk of UTI. Dapagliflozin 10mg/d (91.9%) and canagliflozin 300mg/d (88.8%) ranked first in the female and male subgroups, respectively, according to the probability rankings for GI. Conclusion Current evidence indicated that SGLT-2i did not significantly increase the risk of harm when comparing different doses, except for dapagliflozin 10mg/d, which showed an increased risk of UTI and may be associated with a higher risk of renal impairment and nasopharyngitis. Additionally, compared with placebo and metformin, the risk of GI was notably elevated for empagliflozin 10mg/d, canagliflozin 300mg/d, and dapagliflozin 10mg/d. However, it is important to note that further well-designed RCTs with larger sample sizes are necessary to verify and optimize the current body of evidence. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023396023.